Food, Energy and Environment: is Bioenergy the missing link? - Pavel Ciaian; D'Artis Kancs (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
The present paper studies price linkages between the food, energy and bioenergy markets. We develop a vertically integrated multi-input, multi-output market model with two price transmission channels: a direct biofuel channel and an indirect input channel. We test the theoretical hypothesis by applying time-series analytical mechanisms to nine major traded agricultural commodity prices, including corn, wheat, rice, sugar, soybeans, cotton, banana, sorghum and tea, along with one weighted average world crude oil price. The data consists of 939 weekly observations from January 1993 to December 2010. The empirical findings confirm the theoretical hypothesis that the prices for crude oil and agricultural commodities are interdependent. Commodities not directly used in bioenergy production are also included in the analysis: a USD 1/barrel increase in oil prices and agricultural commodity prices increase by between USD 0.09/tonne and USD 1.65/tonne. Contrary to the theoretical predictions, the indirect input price transmission channel is found to be small and statistically insignificant.
Keywords: C14; C22; C51; Q11; Q13; Q42; 330; Energy; bioenergy; crude oil; prices; food; renewable fuels; cointegration.